2013
DOI: 10.1080/10408398.2011.579697
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Surface Active Agents in Baking Industry: An Overview

Abstract: Different researchers have previously used surfactants for improving bread qualities and revealed that these compounds result in improving the quality of dough and bread by influencing dough strength, tolerance, uniform crumb cell size, and improve slicing characteristics and gas retention. The objective of this review is to highlight the areas where surfactants are most widely used particularly in the bread industries, their role and mechanism of interaction and their contribution to the quality characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 165 publications
1
9
0
Order By: Relevance
“…The values for the softening of the dough is minimum (60.67 BU) in T 1 (0.25% SSL+4% shortening+4%water) and maximum (122.3 BU) in T 15 (0.75% GMS+3.50% shortening+4%water). The results of present studies indicate that GMS gels T 15 (0.75% GMS+3.50% shortening+4%water) T 14 (0.50% GMS+3.75% shortening+4%water) reduce frequency of dough collapse as compared to the T 17 (Control) which is in line with the findings of Ahmad et al (2014). The surfactants form complexes with proteins fractions resulting in delaying softening of dough.…”
Section: Softening Of Doughsupporting
confidence: 89%
See 1 more Smart Citation
“…The values for the softening of the dough is minimum (60.67 BU) in T 1 (0.25% SSL+4% shortening+4%water) and maximum (122.3 BU) in T 15 (0.75% GMS+3.50% shortening+4%water). The results of present studies indicate that GMS gels T 15 (0.75% GMS+3.50% shortening+4%water) T 14 (0.50% GMS+3.75% shortening+4%water) reduce frequency of dough collapse as compared to the T 17 (Control) which is in line with the findings of Ahmad et al (2014). The surfactants form complexes with proteins fractions resulting in delaying softening of dough.…”
Section: Softening Of Doughsupporting
confidence: 89%
“…The present research shows that treatments T 2 (0.50% SSL+3.75% shortening+4%water), T 6 (0.50% CSL+3.75% shortening+4%water), T 9 (0.25% PS-60+4% shortening+4%water) and T 13 (0.25% GMS+4% shortening+4% water) in SSL, CSL, PS-60 and GMS respectively resulted in highest moisture content as compared to the T 17 (Control) which may be due to interaction of surfactants with amylose fractions. The increase in moisture content is formation of complexes between the surfactants and amylopectin molecules which cause reduction in granule swelling by reducing starch polymer mobility and results in less crystallization (Ahmad et al, 2014). The hydrophilic nature of the surfactants may be another reason for the increase moisture content in all the treatments as compared to the control as the surfactants complexes resulted in overall baking process may results as obstacle to the gas diffusion, lessening water vapors losses and rising the final moisture content of the loaves.…”
Section: Moisture Contentmentioning
confidence: 99%
“…It has been a part of the human diet for thousands of years. Different researches have indicated that flaxseed contains various substances that appear to have several health benefits including omega‐3 fatty acids, fiber, lignans, and protein (Ahmad et al, ; Oomah, ).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of C12, C14, C16, and C18 significantly increased loaf volume in the CSP (Sawa et al 2009). DATEM can form tight linkages with gliadins in the form of lamellar liquid-crystalline phases (Ribotta et al 2004), which aids extension of gas cells and enhances dough elasticity and bread volume (Turabi et al 2008;Ahmad et al 2014). Anionic surfactants such as DATEM are also known to increase loaf volume significantly.…”
mentioning
confidence: 99%